Study of the interaction of the oxidoreductase laccase of Pleurotus ostreatus with gold nanoparticles and phenolic compounds through empirical and in silico techniques (2021)
Maestría en ingeniería química enfocada en bioprocesos, metodos computacionales, experimentales, bioinformática y diseño de experimentos con análisis probabilísticos